Digital Authentication Usage Behavior of Indonesian Civil Servant Pensioners - Zul Akbar Yulianto; Linda Asriani; Ardian Syaputra; Julbintor Kembaren (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In improving service and payment accuracy for Civil Servant pensioners in Indonesia, pensioners can already use a validation tool in digital authentication through facial biometric data using smartphone applications in 2019. This authentication activity is something that pensioners must do before getting their monthly pension to ensure they are still alive and entitled to retirement. With the development of this digital service, pensioners can conveniently fulfil their obligations. However, to ensure pensioners can adapt to technological changes, these services are essential in ensuring the success of the service digitization program. It is because, demographically, there are still many pensioners belonging to the Baby Boomer and X generation categories. This study was conducted to determine the factors that influence the Behavior Intention and Digital Authentication Usage Behavior in pensioners, using TAM 3 theories moderated by technology experience factors from pensioners. Meanwhile, few studies discuss technology experience as a moderator in knowing these two variables. As a result, there was a positive and significant effect of Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Perceived Enjoyment (PE) on Behavioral Intention (BI) using Digital Authentication Applications. Furthermore, Behavioral Intention (BI) positively and significantly influenced the Usage Behavior (UB) of this Digital Authentication. Meanwhile, Experience did not moderate the positive effect of perceived enjoyment on behavior intention of the TASPEN Otentikasi Application.